2015
DOI: 10.1080/2162402x.2015.1078057
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virotherapy for treatment of breast cancer, including triple-negative breast cancer

Abstract: Breast cancer is a heterogeneous disease, characterized by several distinct biological subtypes, among which triple-negative breast cancer (TNBC) is one associated with a poor prognosis. Oncolytic virus replication is an immunogenic phenomenon, and viruses can be armed with immunostimulatory molecules to boost virus triggered antitumoral immune responses. Cyclophosphamide (CP) is a chemotherapy drug that is associated with cytotoxicity and immunosuppression at higher doses, whereas immunostimulatory and anti-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…41,199 Along the lines of our Trial Watch series, here we discuss recent preclinical and clinical advances in the development of ICD-inducing chemotherapeutic regimens. 200 Several other interventions that trigger bona fide ICD, such as radiation therapy administered according to specific regimens, 94,[201][202][203] high hydrostatic pressure, 3,4 oncolytic virotherapy [204][205][206][207][208] and photodynamic therapy, 44,86,98,99 are not discussed here in further detail.…”
Section: Introductionmentioning
confidence: 99%
“…41,199 Along the lines of our Trial Watch series, here we discuss recent preclinical and clinical advances in the development of ICD-inducing chemotherapeutic regimens. 200 Several other interventions that trigger bona fide ICD, such as radiation therapy administered according to specific regimens, 94,[201][202][203] high hydrostatic pressure, 3,4 oncolytic virotherapy [204][205][206][207][208] and photodynamic therapy, 44,86,98,99 are not discussed here in further detail.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that the MDA-MB-436 human TNBC cell line, when treated with a triple combination of TMZ; 4-hydroperoxycyclophosphamide (4-HPCP); an active metabolite of the prodrug cyclophosphamide (CP); and Ad5/3-D24-GMCSF, a 5/3-capsid chimeric OAd coding for GM-CSF, had increased immunogenic cell killing and autophagy [ 31 ]. In another study, it was reported that CP at low doses increased the efficacy of Ad5/3-DM4-GMCSF in MDA-MB-436 cells, and similar effects were observed in an orthotopic TNBC xenograft mouse model [ 35 ].…”
Section: Discussionmentioning
confidence: 79%
“…Current trends of oncolytic Ad development for clinical applications have focused on armed oncolytic Ads expressing anticancer therapeutic genes. Several clinical studies have evaluated the efficacy of these Ads against various types of cancers . In the context of this strategy, we generated oncolytic Ad expressing DCN, a potent inducer of tumor cell apoptosis and ECM degradation, as a potential candidate for the treatment of desmoplastic pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%